Systematic Literature Review: Effects of Different Forms of Iron Supplementation on Gut Microbiota Composition and Immune Function in Children with Iron Deficiency Anemia - Firda Nur Laila; Ardita Fara (The International Journal of Medical Science and Health Research, 2025)
Background: Iron deficiency anemia (IDA) is a public health concern with this major global health concern seeming to be affecting the child population more, since it can prove detrimental to growth, cognitive functioning, and immune function. Though iron supplementation is the primary intervention for IDA treatment, its effects on gut microbiota and immune function are still not fully understood. Different forms of supplementation might have different effects on the gut microbiome and immunity. Methods: This systematic review examined studies published between 2014 and 2024 using electronic databases including PubMed, Scopus, and Cochrane Library. This review, abiding by the guidelines of PRISMA and following the PICOS construction, deals with children of ages comprising 0-12 years, diagnosed with IDA, investigating the various modes of delivering iron such as nano-iron, fortified foods, oral or parenteral iron, and their influence on gut microbiota composition and immune function. Results: Studies report variable responses of iron supplementation on gut microbiota and immunity based on formulation, dosage, and concurrent nutrient administration. Some studies show that there is no considerable change to the gut microbiota profiles resulting from synbiotic additions; however, they have also linked IDA with microbial dysbiosis. High-dose iron interventions tend to disrupt the gut microbiota and significantly increase the chances of infection, especially in settings with poor hygiene. On the other hand, even prebiotics have been tried to alleviate this side effect besides continuing iron therapies. Conclusion: Iron supplementation is necessary for treating IDA in children, and the effect on gut microbiota and immunity depend on various factors. The administration of prebiotics or adjusting doses could minimize side effects and benefit treatment. Future studies should be conducted with a focus on personalized intervention considering diet, environment, and microbiological factors to better manage IDA and alleviate adverse effects.